Pemanfaatan Boil-Off Gas Sebagai Bahan Bakar Kapal Pengangkut Gas - Ikhwan Ikhwan; Hamdani Hamdani; Ahmad Syuhada (Jurnal Teknik Mesin Unsyiah, 2014)
LNG carrier is the most reliable primary means of transportation of LNG in the world. In operation, each LNG carrier would result in boil-off gas from the cargo hold due to the expansion. BOG The average amount that can be produced is 0.15% of the tank capacity and unloading space per day. For that, there is great opportunity in the use of BOG as fuel in LNG carrier resulting in fuel savings. One of the driving forces that can take advantage of BOG is a Combined Cycle Propulsion Plant (CCPP) of a gas turbine and a steam turbine, a gas turbine with HRSG and dual fuel technology for generating thermal energy from the exhaust gas of gas turbines. Improved efficiency and are able to use as fuel BOG will be able to lower the fuel oil consumption of the driving force. The study was conducted by comparing the fuel consumption of LNG carrier propulsion system with a conventional steam turbines, compared to the LNG carrier using the CCPP. CCPP eventually be an option with the highest fuel economy both in terms of BOG utilization, efficiency and fuel use. For the 138,000 m3 LNG carrier of the same, with the CCPP do MDO-fueled fuel savings of U.S. $ 46,117.80 per day and for using the CCPP BOG, fuel savings of U.S. $ 56,472.70 per day.